2004
DOI: 10.1074/jbc.m403525200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Protein Kinase C ϵ Inhibits the Two-pore Domain K+ Channel, TASK-1, Inducing Repolarization Abnormalities in Cardiac Ventricular Myocytes

Abstract: Activation of the platelet-activating factor (PAF) receptor leads to a decrease in outward current in murine ventricular myocytes by inhibiting the TASK-1 channel. TASK-1 carries a background or "leak" current and is a member of the two-pore domain potassium channel family. Its inhibition is sufficient to delay repolarization, causing prolongation of the action potential duration, and in some cases, early after depolarizations. We set out to determine the cellular mechanisms that control regulation of TASK-1 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 28 publications
3
37
0
Order By: Relevance
“…4B; p Ͻ 0.01). To verify the requirement for PKC⑀ in the C-PAF-induced inhibition of the TASK-1 current, in agreement with previous observations in the murine channel, a specific PKC⑀-inhibitor peptide was used (7,18). Addition of this peptide but not a scrambled control peptide to the patch pipette (100 nM) blocked the effect of C-PAF on all previously responsive forms of the channel ( Fig.…”
Section: Peri-operative Af Is Associated With Neutrophil Influx and Psupporting
confidence: 78%
See 4 more Smart Citations
“…4B; p Ͻ 0.01). To verify the requirement for PKC⑀ in the C-PAF-induced inhibition of the TASK-1 current, in agreement with previous observations in the murine channel, a specific PKC⑀-inhibitor peptide was used (7,18). Addition of this peptide but not a scrambled control peptide to the patch pipette (100 nM) blocked the effect of C-PAF on all previously responsive forms of the channel ( Fig.…”
Section: Peri-operative Af Is Associated With Neutrophil Influx and Psupporting
confidence: 78%
“…It has long been known that activated neutrophils contribute to arrhythmogenicity in isolated hearts, and numerous clinical studies have found a link between inflammatory mediators and arrhythmias. We have described repolarization abnormalities caused by the inflammatory mediator PAF, released from activated neutrophils (5), and we determined that C-PAF elicits these effects in vitro via PKC⑀-dependent inhibition of the TASK-1 channel in murine ventricular myocytes (6) and in heterologous expression systems (7). We have now demonstrated a similar phenomenon in intact canine atrium and associated with peri-op AF in the dog.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations